Spontaneous Adrenal Hemorrhage with Mild Hypoadrenalism in a Patient Anticoagulated with Apixaban for Antiphospholipid Syndrome: A Case Report and Literature Review. (30th November 2022) - Tan, Jia Wei; Shukla, Anant; Hu, Jiun-Ruey; Majumdar, Sachin K.
Abstract : Background . Adrenal hemorrhage (AH) is a serious endocrine complication of antiphospholipid syndrome (APLS). Case Presentation . We report a 45-year-old man who presented with several deep venous thromboses and was initially treated with apixaban, who later developed bilateral AH. Laboratory findings were consistent with cortisol deficiency yet preserved aldosterone physiology. He was diagnosed with APLS and treated with warfarin. After 8 months of follow-up, he remained on cortisol replacement with no evidence of recovery. We reviewed PubMed/MEDLINE indexed articles from 1950 to 2022 for cases of AH in APLS patients on anticoagulation. Six cases of patients on direct oral anticoagulants (DOACs) were reported. Discussion . The unique vasculature of the adrenal glands creates a "functional vascular dam" in the zona reticularis, which is susceptible to thrombosis in situ and hemorrhage. DOACs may further increase the risk of AH. Conclusion . Depending on the degree of adrenal involvement in AH, patients can present with partial or complete primary adrenal insufficiency. More data are needed to characterize adrenal function after AH, and the safety of DOAC versus warfarin in patients with APLS warrants further studies.